(untitled) (Journal of the College of Basic Education, 2024)
The study aims to explain the saying of the Noble Messenger (may God bless him and his family and grant them peace) (No harm, no harm), which was considered one of the major rules that jurists rely on in incidents and new issues as a guide for him. That is why I saw many of them using it as evidence; Which prompted me to read about this rule, what is its origin and meaning, to find how the jurists were building most of the chapters of jurisprudence on it and ruling on its issues. Indeed, most of them believe that it is sufficient to return the entire Islamic jurisprudence to this rule, and thus it became clear to me that the greatest purpose of Sharia law is to bring about righteousness. And ward off Corruption, if we know that the interest is bringing benefit and repelling harm, or repelling harm from creation and preventing harm, and that is by preventing it starting with all methods of prevention, ruling to remove it after it occurs, and considering the impact resulting from it to make amends to the harmed and hold accountable the one who caused the harm.